Distribution, Impacts and Management Option for Water Hyacinth (Eichhnornia Crassipes [Mart.] Solms) in Ethiopia: A Review - Mengist, Yigerm; Moges, Yohannes (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Water hyacinth (Eichhprnia crassipes) is the most dangerous and worst invasive aquatic weed in the worldwide including Ethiopia, and negatively affecting millions of water resources, fisheries, transportation and social structure. Water hyacinth was introduced in the water bodies of the Rift Valley in 68years ago and currently, the weed is distributed Lake Tana, Lake Abaya, Lake Koka, Koka Dam. The wide distribution and abundance of water hyacinth has led to decreased water availability and sustainable water biodiversity in Ethiopian lakes. However, the spread of water hyacinth is threatening not only water biodiversity but also socioeconomic development and human wellbeing. Water hyacinth in water bodies and nearby areas the local stakeholder has its negative impact on environmental problem and it’s influenced aquatics biodiversity. This review paper aimed to investigate the distribution, impacts and its integrated management option against water hyacinth in Ethiopia. Therefore, based on the review it can be concluded that human intervention is considered as the current problem of water resource in the country and further study is needed to sustain the water resource are needed to keep water hyacinth at unproblematic levels.